Organocerium: A New Contender for Halogen–Metal Exchanges - Music, Arif; Didier, Dorian (Synlett, 2019)
In the context of our current research on dependable and sustainable methods for C–C bond-forming reactions, we have recently developed new strategies to generate organocerium reagents through simple bromide–cerium exchanges. n-Bu3Ce enabled a fast and general access to functionalized triaryl- and alkenyl cerium species from the corresponding aryl- and alkenyl bromides. A broad range of these new organocerium species was engaged in Zweifel’s olefination, allowing for the synthesis of widely substituted alkene derivatives in a stereospecific way. Herein, we place the formation of organocerium species in the context of known organometallic reagents (Li, Mg, Zn, Cu, Ca, La, and Sm) generated through halogen–metal exchange reactions and their application in further transformations.
Keywords: organometallic; organocerium; Zweifel olefination; halogen–metal exchange; functional group tolerance